The managing of the (Third) world - Cooke, Bill (2004)
This paper is about the relationship between management, a First World discipline, and the Third World. Management is widely assumed to apply in organizations in modern, or postmodern, societies. However, a distinctive form of management, Development Administration and Management (DAM), exists and is applied to Third World nation-states, which are deemed in the First World to require modernization. This article sets out the Institutional and conceptual separation and crossover between management and DAM. It then goes on to consider DAM in practice, demonstrating how it, and through it management, are complicit in neo-liberal World Bank interventions in the Third World. It concludes by reviewing the implications of the status of DAM, and management, as direct instruments of national-level neo-liberal change. - Reproduced.
Keywords: Management